TCR- and CD28-mediated recruitment of phosphodiesterase 4 to lipid rafts potentiates TCR signaling. - Abrahamsen, H; Baillie, G; Ngai, J; Vang, T; Nika, K; Ruppelt, A; Mustelin, T; Zaccolo, M; Houslay, M; Taskén, K (2004)
Ligation of the TCR along with the coreceptor CD28 is necessary to elicit T cell activation in vivo, whereas TCR triggering alone does not allow a full T cell response. Upon T cell activation of human peripheral blood T cells, we found that the majority of cAMP was generated in T cell lipid rafts followed by activation of protein kinase A. However, upon TCR and CD28 coligation, beta-arrestin in complex with cAMP-specific phosphodiesterase 4 (PDE4) was recruited to lipid rafts which down-regulated cAMP levels. Whereas inhibition of protein kinase A increased TCR-induced immune responses, inhibition of PDE4 blunted T cell cytokine production. Conversely, overexpression of either PDE4 or beta-arrestin augmented TCR/CD28-stimulated cytokine production. We show here for the first time that the T cell immune response is potentiated by TCR/CD28-mediated recruitment of PDE4 to lipid rafts, which counteracts the local, TCR-induced production of cAMP. The specific recruitment of PDE4 thus serves to abrogate the negative feedback by cAMP which is elicited in the absence of a coreceptor stimulus.